2010
DOI: 10.1164/rccm.200909-1451oc
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Vasoactive Intestinal Peptide Exerts Immunoregulatory Effects in Sarcoidosis

Abstract: This study is the first to show the immunoregulatory effect of VIP in humans, and supports the notion of inhaled VIP as an attractive future therapy to dampen exaggerated immune responses in lung disorders. Thus, the inhalation of neuropeptides may be developed into a new therapeutic principle for chronic inflammatory lung disorders in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
117
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(121 citation statements)
references
References 34 publications
1
117
0
1
Order By: Relevance
“…An interesting study by PRASSE et al [27] reported on treatment of pulmonary sarcoidosis with inhaled vasoactive intestinal peptide. Treatment with vasoactive intestinal peptide was associated with significant changes in the release of several cytokines by alveolar macrophages retrieved by BAL.…”
Section: Other Agentsmentioning
confidence: 99%
“…An interesting study by PRASSE et al [27] reported on treatment of pulmonary sarcoidosis with inhaled vasoactive intestinal peptide. Treatment with vasoactive intestinal peptide was associated with significant changes in the release of several cytokines by alveolar macrophages retrieved by BAL.…”
Section: Other Agentsmentioning
confidence: 99%
“…110 No adverse effects were reported after any of these trials. These results support the potential therapeutic role of inhaled vasoactive intestinal peptide agonists in treating asthma, pulmonary hypertension, and sarcoidosis.…”
Section: Vasoactive Intestinal Peptidementioning
confidence: 93%
“…Based on these functions of the peptide, several clinical trials have been reported using VIP or its analog for asthma [45] and sarcoidosis [46]. Linden et al performed a double-blind, randomized, placebo controlled, crossover study for twenty four patients with moderate stable asthma [45].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…They concluded that inhalation of a Ro25-1553 constituted a promising approach for bronchodilation in patients with asthma. Prasse A, et al reported their open clinical Phase II study where they treated twenty patients with histologically proved sarcoidosis with nebulized VIP for 4 weeks [46]. VIP inhalation significantly reduced production of tumor necrosis factoralpha by cells isolated from bronchoalveolar lavage CD4(+)CD127(-)CD25(+) T cells [46].…”
Section: Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation